(untitled) (Strathmore Law Review, 2025)
Some parents and/or guardians are actively sharing photographs, videos, and even personal details of their children across various social media platforms in Kenya to share their parental experiences. This concept has been dubbed ‘sharenting.’ This research will employ the interest theory of rights to examine the possible contradiction between children’s ever-evolving right to privacy and parents’ and/or guardians’ freedom of expression on social media platforms. The study promotes a reasonable approach that prioritises the child’s best interests while still acknowledging parental freedom of self-expression. The developing nature of children’s rights and the possible drawbacks of unrestricted online exposure are emphasised. This work examines statutes, case laws, books, journals, and reports about these rights and their various conceptions. It will shed light on Kenya’s legal framework for safeguarding children’s online privacy rights and investigate the possible violations caused by parental online sharing practices. The purpose of this study is to add to the current legal and social debates in Kenya around children’s rights to privacy online, and it stresses the importance of striking a balance between parental freedom of expression and the protection of children’s right to privacy on digital platforms.